Diversidade genética em soja com diferentes níveis de resistência ao Sclerotinia sclerotiorum, correlações, análise de trilha e população de plantas - Machado, Beliza Queiroz Vieira (2017)
Currently, due to the agro-industrial complex established in the country, soy is among the main crops of Brazilian agribusiness. The production technologies development and genetic improvement of those species have led to expansion of agricultural frontiers and increase of the national yield. Breeding programs have aimed to obtain genotypes that are also productive and resistant against pests and diseases, such as white mold caused by Sclerotinia sclerotiorum. The narrow genetic basis of Brazilian soybean has being pointed by researches that highlight the importance of genetic diversity studies with the purpose of assisting selection of parents aiming hybridizations. Selection of superior lines is another important point since the majority of target features in soybean breeding have a quantitative nature. From this perspective, information on correlations between characters and path analysis helps to improve breeding strategies definition. Once superior lines are selected, they are released as new cultivars. In addition, knowledge about crop management, such as the adequate size related to plant population density, is fundamental. In this context, this study aimed to evaluate the soybean genetic divergence regarding different levels of resistance to white mold; to study correlations between characters and path analysis and to evaluate influence of sowing density on grain yield and on morph agronomic features of soybean. Two experiments were carried out under field conditions in the Capim Branco farm of the Federal University of Uberlândia. The first experiment was make up by 24 soybean genotypes evaluated in a randomized complete block design with three replicates. All agronomic traits has shown genetic variability. Genotypes UFU B7, UFU B14, UFU B16, Msoy-6101 and UFU B5 were verified as early-cycle; UFU B1, UFU B3, UFU B8 and UFU B16 genotypes have showed high grain yield. Genotypes UFU B1, UFU B2, UFU B3, UFU B4, UFUS 7910, UFU B6, UFU B7, UFU B9 and UFU 20 were resistant regarding the length of lesion caused by S. sclerotiorum. The Genotypes were placed within four groups by the Tocher and UPGMA methods. Feature that most contributed to genetic diversity was the number of days to the blooming. Phenotypic and genotypic correlations and path analysis have indicated the number of pods with three grains as the feature of better effect on grains yield. In the second experiment genotypes UFU LVR, UFUS 7910 and UFUS 8301 were evaluated regarding population densities by a randomized complete block, design with four replications (12, 14, 16, 18 pl m-1). Interactions between genotypes and densities were significant for most characters. Plants height at maturity with increasing sowing density was reduced for cultivar UFUS 7910, as well for the three genotypes, there was a reduction in grain yield with increasing sowing density. Regarding UFUS LRV line, the most indicated plant population density is between 12 and 16 pl m-1. Recommended population density for UFUS 7910 is 12 pl m-1. In relation to the sowing of UFUS 8301 is indicated population sizes between 12 to 14 pl m-1.